Keterkaitan Arah Kebijakan Lingkungan Pasca Undang-Undang Tentang Cipta Kerja dengan Manajemen dan Kebijakan Lingkungan Sektor Militer - Endro Tri Susdarwono; Eko Susdarwanto (Fakultas Hukum Universitas PGRI Palangkaraya, 2021)
The practice of the Job Creation Law related to the environment affects the management of the military environment in the form of preparing and structuring the country's territory as a defense field and preparing regional logistics. This study aims to examine the relationship between the direction of development after the Cipta Kerja Law with environmental management and policies in the environmental sector. In this research, the approach used is a combination of qualitative and quantitative. The qualitative approach method used is juridical normative analytical legal substance, while the quantitative approach uses hypothesis testing on signs in order to analyze the impact arising from the occurrence of a thing. The conclusion from this research is that the Job Creation Law in its implementation has the potential to weaken instruments related to environmental management and policy in the military sector, namely environmental protection, community rights and also has the potential to have a negative impact on environmental quality. This is also reinforced by the results of hypothesis testing on signs that there is a change in building a standard environmental management response that must be used for all components, civil or military.